Louis Armstrong, an American genius - Collier, James Lincoln, 1928- (OUP E-Books., 1983)
Louis Armstrong. "Satchmo." To millions of fans, he was just a great entertainer. But to jazz aficionados, he was one of the most important musicians of our times--not only a key figure in the history of jazz but a formative influence on all of 20th-century popular music. Set against the backdrop of New Orleans, Chicago, and New York during the "jazz age", Collier re-creates the saga of an old-fashioned black man making it in a white world. He chronicles Armstrong's rise as a musician, his scrapes with the law, his relationships with four wives, and his frequent feuds with fellow musicians Earl Hines and Zutty Singleton. He also sheds new light on Armstrong's endless need for approval, his streak of jealousy, and perhaps most important, what some consider his betrayal of his gift as he opted for commercial success and stardom. A unique biography, knowledgeable, insightful, and packed with information, it ends with Armstrong's death in 1971 as one of the best-known figures in American entertainment.